(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: To study the nuclear structure, a novel model known as the interacting boson model-one (IBM-1) is utilized. It is hypothesized that low-lying collective quadrupole states can be produced as states of an N-boson system capable of occupying two levels, other with angular momentum J = 0 and one with angular momentum J = 2. Materials and Methods: We investigated the nuclear structure of Molybdenum in the theoretical context. We utilized the Interacting Boson Model (IBM-1) to discover the appropriate Hamiltonian for investigating -isotope in this work. Results: To generate the Hamiltonian, we calculated energy levels (ground, beta and gamma) bands and B(E2) transitions for the -isotope using the best-suited parameter values. Conclusions: According to this study and the IBM test results, has a transition behavior of SU(5) limitations. When the results are compared with the experimental data, they show good agreement.